Six hundred years of South American tree rings reveal an increase in severe hydroclimatic events since mid-20th century - Morales, Mariano S.; Cook, Edward R.; Barichivich, Jonathan; Christie, Duncan A.; Villalba, Ricardo; LeQuesne, Carlos; Srur, Ana M.; Ferrero, M. Eugenia; Gonzalez-Reyes, Alvaro; Couvreux, Fleur; Matskovsky, Vladimir; Aravena Donaire, Juan Carlos; et al. (My University, 2020)
South American (SA) societies are highly vulnerable to droughts and pluvials, but lack of long-term climate observations severely limits our understanding of the global processes driving climatic variability in the region. The number and quality of SA climate-sensitive tree ring chronologies have significantly increased in recent decades, now providing a robust network of 286 records for characterizing hydroclimate variability since 1400 CE. We combine this network with a self-calibrated Palmer Drought Severity Index (scPDSI) dataset to derive the South American Drought Atlas (SADA) over the continent south of 12 degrees S. The gridded annual reconstruction of austral summer scPDSI is the most spatially complete estimate of SA hydroclimate to date, and well matches past historical dry/wet events. Relating the SADA to the Australia-New Zealand Drought Atlas, sea surface temperatures and atmospheric pressure fields, we determine that the El Nino-Southern Oscillation (ENSO) and the Southern Annular Mode (SAM) are strongly associated with spatially extended droughts and pluvials over the SADA domain during the past several centuries. SADA also exhibits more extended severe droughts and extreme pluvials since the mid-20th century. Extensive droughts are consistent with the observed 20th-century trend toward positive SAM anomalies concomitant with the weakening of midlatitude Westerlies, while low-level moisture transport intensified by global warming has favored extreme rainfall across the subtropics. The SADA thus provides a long-term context for observed hydroclimatic changes and for 21st-century Intergovernmental Panel on Climate Change (IPCC) projections that suggest SA will experience more frequent/severe droughts and rainfall events as a consequence of increasing greenhouse gas emissions.
Keywords: drought atlas; palaeoclimate reconstruction; extreme hydroclimate events; south america hydroclimate; southern hemisphere climate modes